(untitled) (Journal of Global Humanities and Social Sciences, 2024)
Universities, local governments, and primary and secondary schools are jointly committed to building a "trinity" professional talent training quality assurance system, providing a good platform for the cultivation of physical education professionals. However, issues such as low identification with roles among entities in the "trinity" model, lack of unified organizational management, insufficient perspective-taking among entities, and conflicting work objectives have affected the effectiveness of the "trinity" model in nurturing talents. There is an urgent need to enhance communication and cooperation among entities, establish and improve the organizational management system, set up a responsibility implementation mechanism, and build a professional development community, so as to form a stable "trinity" physical education professional talent training model, promoting high-quality development of school physical education.